2017
DOI: 10.1007/s11356-017-8855-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mode of action of violacein from Chromobacterium violaceum UTM5 against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: Violacein, violet pigment produced by Chromobacterium violaceum, has attracted much attention recently due to its pharmacological properties including antibacterial activity. The present study investigated possible antibacterial mode of action of violacein from C. violaceum UTM5 against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) strains. Violet fraction was obtained by cultivating C. violaceum UTM5 in liquid pineapple waste medium, extracted, and fractionated using ethyl acetate and vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 64 publications
2
41
0
1
Order By: Relevance
“…Recently, more and more studies have shown the presence of mesosomes in bacteria cells after treatment with antimicrobial drugs, suggesting mesosomes may be important to bacteria for responding to and surviving exposure to antibiotics. Several antibiotic efficacy studies have been performed with S. aureus and/or MRSA, including retinoids (Kim et al, 2018), violacein (Aruldass et al, 2018), defensins (Shimoda et al, 1995), trimethoprim (Nishino et al, 1987), rifampin (Gottfredsson et al, 1993), cationic peptides (Friedrich et al, 2000), tetrabromobisphenol A (Wang et al, 2018), antimicrobial peptides (Hartmann et al, 2010), photodynamic therapy (Iluz et al, 2018), porphyrins (Malik et al, 1988), silver nanoparticles (Krychowiak et al, 2018). In addition, imipenem has been studies with P. aeruginosa (Gottfredsson et al, 1993) and rifampicin has been studies with Xanthomonas campestris (Li et al, 2008) and E. coli (Xin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have shown the presence of mesosomes in bacteria cells after treatment with antimicrobial drugs, suggesting mesosomes may be important to bacteria for responding to and surviving exposure to antibiotics. Several antibiotic efficacy studies have been performed with S. aureus and/or MRSA, including retinoids (Kim et al, 2018), violacein (Aruldass et al, 2018), defensins (Shimoda et al, 1995), trimethoprim (Nishino et al, 1987), rifampin (Gottfredsson et al, 1993), cationic peptides (Friedrich et al, 2000), tetrabromobisphenol A (Wang et al, 2018), antimicrobial peptides (Hartmann et al, 2010), photodynamic therapy (Iluz et al, 2018), porphyrins (Malik et al, 1988), silver nanoparticles (Krychowiak et al, 2018). In addition, imipenem has been studies with P. aeruginosa (Gottfredsson et al, 1993) and rifampicin has been studies with Xanthomonas campestris (Li et al, 2008) and E. coli (Xin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…B. As expected based on the known activities of violacein (Choi et al ., ; Im et al ., ; Aruldass et al ., ), the purified sample was very potent towards this bacterium, with 3.1 mg/l significantly reducing both its bioluminescence (99.8% loss; Figs B, C and Supporting Information S6) and viability (6‐log reduction; Fig. D) by 6 h. The wild‐type MVs were also bactericidal towards this strain of S. aureus , with the same concentration causing a 90.7% loss in bioluminescence and an 85% loss in viability.…”
Section: Resultsmentioning
confidence: 88%
“…Most strikingly, CaCO 3 was found to be a superior supplement to buffer media pH. The carbonate group (CO 3 2-) will effectively neutralize the organic acids accumulated during the fermentation. At the end of the fermentation, 70.04 mg/L violacein and 5.28 mg/L deoxyviolacein were produced from the yeast culture supplemented with CaCO 3 , with violacein purity up to 86.92%.…”
Section: Ph Optimization In Shake Flask Fermentationmentioning
confidence: 99%
“…Violacein and deoxyviolacein belong to bisindol pigments with deep purple color, which are derived from tryptophan biosynthetic pathway and naturally produced by a number of marine bacteria such as Janthinobacterium lividum [1,2], Chromobacterium violaceum [3][4][5], Pseudoalteromonas luteoviolacea [6], et al Clinical trials and biomedical studies indicate both compounds possess strong antibacterial [7,8], anticancer [9], antiviral [10], trypanocidal [11] and antiprotozoal [12] properties. These characteristics make violacein a superior chemical scaffold and drug candidate for the development of clinically active agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation